INTEGRATION IN TEACHING TOXICOLOGY: CROSS-ROADS AND THE WAY FORWARD - Gupta, Sanjay; Das, Abhishek; Gupta, Nikita (Journal of Forensic Medicine and Toxicology, 2024)
Introduction: The study of the harmful effects of chemicals and substances on the human body and environment is called toxicology, an important branch of medical science. The subject toxicology also deals with features of presentation on the human body and environment along with its methods of detection and treatment. Different toxins and poisonous substances affect differently based on various external and internal factors. Importance of Integration: It is important to teach medical students in undergraduate and postgraduate level toxicology in detail for the effective management of patients. Competency-based medical education has been implemented by the National Medical Commission which mandates integrated teaching of toxicology keeping it aligned with other stakeholder subjects like medicine, pharmacology, biochemistry, and others.